ECONOMIC ANALYSIS OF EDUCATION IN POST-WAR AMERICA: NEW INSIGHTS FROM THEODORE SCHULTZ AND JOHN KENNETH GALBRAITH. Issue 1 (March 2020) - Chirat, Alexandre; Le Chapelain, Charlotte
Abstract : Human capital theory has suffered much criticism. The filter theory of education (Arrow 1973), the theory of education as a "signal" (Spence 1973), and the theory of "screening" (Stiglitz 1975), for instance, have seriously challenged it from within mainstream economics, and heavy criticism has also come from other paradigms, with Franck Bailly (2016) recently documenting the critique from the radical school. Within this set of ideas that flourished in the post-WW II period and challenged human capital theory, John Kenneth Galbraith's analysis of the dynamics of the education process is often neglected. In his original institutionalist and firm-based approach to the evolution of education, Galbraith placed great emphasis on the issue of the requirements of the planning system when he tackled the issue of human capital investment. More surprisingly—since he is unanimously recognized as the "founding father" of the "human capital revolution"—Theodore Schultz himself developed a substantial critique of human capital theory that shares some ground with Galbraith's. The aim of this contribution is to provide new insights into the history of post-WW II ideas in the field of economics of education by reviewing Schultz's and Galbraith's respective analyses of education and highlighting their proximities. Both authors raise doubts regarding the idea that the aggregation of individual choices must be regarded as the relevant generative mechanism of the dynamic of education and the basis of the allocation of education resources. Consequently, both question the equivocal concept of student sovereignty.